A method for preparing multifunctional conductive foam
By using three-dimensional graphite foam-loaded nanocobalt and melamine polyphosphate in conductive foam, the problems of poor conductivity and insufficient flame retardant performance are solved, and efficient electromagnetic shielding and flame retardant effects are achieved.
Patent Information
- Application Number
- CN202411281473.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing conductive foam has poor electrical conductivity and uneven electrical conductivity, which seriously affects its shielding effect. At the same time, it lacks flame retardant performance and cannot fully meet market requirements.
A three-dimensional graphite foam loaded nanocobalt is used to prepare conductive agents, and cross-link with melamine polyphosphate is used to prepare flame retardant conductive agents, and foaming is combined with polyether polyol, isocyanate and foaming agent. After maturation, multifunctional conductive foam is prepared.
The conductive foam is significantly improved and flame retardant properties are ensured, ensuring its efficient performance in shielding and heat dissipation, while maintaining the lightweight, flexibility and durability of the foam.
Smart Images

Figure CN118956284B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of foam, and in particular to a method for preparing multifunctional conductive foam. Background Art
[0002] Foam is a material made of foamed plastic particles, referred to as foam. Foam has a series of characteristics such as elasticity, light weight, fast pressure-sensitive fixation, easy use, and easy bending.
[0003] Conductive foam is particularly suitable for occasions with limited capacity and closing pressure, and has low cost. It is particularly suitable for use in occasions that require good fit and high-performance shielding. It can be widely used in electronic chassis, housings, indoor chassis, industrial equipment, laptops, mobile communication equipment, etc. However, the existing conductive foam has poor conductivity and uneven conductivity, which seriously affects the shielding effect of the conductive foam. On the other hand, electronic products are constantly updated, their working components are becoming more and more sophisticated, the speed and efficiency of work are getting higher and higher, and the heat generation is also getting higher and higher. Therefore, it is not only required to be equipped with corresponding heat dissipation foam, but also to have flame retardant ability to avoid excessive temperature and cause flammable products to become flammable.
[0004] Most of the conductive foams in the prior art use conductive carbon black as the conductive medium. Therefore, not only is the amount of conductive medium added too large, it is easy to contaminate the contact objects and reduce the mechanical properties of the foam. However, if the amount of carbon black added is reduced, its conductivity will be low. At the same time, they do not have flame retardant properties and cannot fully meet market requirements. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a method for preparing a multifunctional conductive foam to solve the problems of poor flame retardancy and low electrical conductivity of the conductive foam in the prior art.
[0006] The purpose of the present invention is mainly achieved through the following technical solutions:
[0007] A method for preparing a multifunctional conductive foam comprises the following steps:
[0008] (1) preparing a conductive agent by loading nano-cobalt on three-dimensional graphite foam, and then cross-linking the conductive agent with melamine polyphosphate to prepare a flame-retardant conductive agent;
[0009] (2) vacuum dehydrating the polyether polyol at 130-140° C. until the moisture content is no more than 0.5%, thereby obtaining a treated polyether polyol;
[0010] (3) adding 2-2.5 parts of a catalyst, 100 parts of a polyether polyol, and 1-5 parts of an antioxidant into a reaction kettle, and reacting at 220-240° C. for 1-2 hours to obtain a reaction material;
[0011] (4) adding 10-18 parts of flame retardant conductive agent, 25-35 parts of isocyanate, 1-2 parts of foaming agent and 2-5 parts of foam stabilizer to the reaction material for foaming at a foaming temperature of 80-85° C. for a reaction time of 20-30 min to obtain a foamed body, and subjecting the foamed body to a aging treatment at 40-60° C. to obtain a foam;
[0012] (5) Using a bonding machine to bond the foam to the conductive cloth; evenly applying an adhesive layer on the side of the foam away from the conductive cloth, and then pressing the foam with the adhesive layer onto the isolation layer to obtain the multifunctional conductive foam.
[0013] Preferably, the specific preparation process of the flame retardant conductive agent is:
[0014] S1: 2-4 portions of nano-cobalt powder are put into a reactor, and a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9 is added, followed by ultrasonic dispersion. After reacting for 30-60 minutes, the product is filtered and washed with anhydrous ethanol for 2-3 times, and then vacuum dried to obtain oleic acid-nano-cobalt; the mass ratio of the nano-cobalt powder to oleic acid is 12-20:1;
[0015] S2: ultrasonically dispersing 2-4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 5-8 parts of thiophene and 0.1-0.2 parts of hydrogen peroxide, stirring and reacting at 40-60° C. for 40-60 minutes, and then performing solid-liquid separation, washing the obtained solid with ethanol and drying it to obtain polythiophene-coated nano cobalt;
[0016] S3: pre-treating the three-dimensional graphene foam in an air atmosphere for 2-5 minutes in a plasma treatment machine, then rinsing with anhydrous ethanol and drying for use; ultrasonically dispersing 10 parts of the pre-treated graphene and 2-4 parts of the polythiophene-coated nano-cobalt in a reactor containing 100 parts of an ethanol aqueous solution and stirring evenly, then adding 0.1-0.3 parts of sodium sulfite to the reactor, stirring and reacting for 30-60 minutes under a nitrogen atmosphere, then filtering and washing the solid with anhydrous ethanol for 2-3 times and then vacuum drying; obtaining a graphene-loaded nano-cobalt conductive agent;
[0017] S4: ultrasonically disperse 30-40 parts of melamine polyphosphate, 8-10 parts of resorcinol and 10 parts of the conductive agent in acetone, uniformly react at 50-70°C for 3-6 hours, centrifuge for solid-liquid separation, then wash with ethanol and dry to obtain a flame retardant conductive agent.
[0018] In one or more embodiments, the conductive cloth layer is a plain woven conductive cloth with a thickness of 40 μm-120 μm.
[0019] In one or more embodiments, the adhesive layer is a pressure-sensitive adhesive or a hot-melt adhesive, and has a thickness of 10-15 μm.
[0020] In one or more embodiments, the isolation layer is release paper with a thickness of 20-30 μm.
[0021] In one or more embodiments, the antioxidant is one of antioxidant 5057, antioxidant 168 and antioxidant 1010.
[0022] In one or more embodiments, the foam stabilizer is one or more of polyacrylamide and dimethyl silicone oil.
[0023] In one or more embodiments, the catalyst is one or more of stannous octoate, stannous isooctanoate and dibutyltin dilaurate.
[0024] In one or more embodiments, the blowing agent is water or a mixture of water and 1,1-dichloro-1-fluoroethane.
[0025] Principle of the present invention:
[0026] Melamine polyphosphate (MPP) is a nitrogen-phosphorus flame retardant whose molecules contain gas source (melamine) and acid source (phosphoric acid) substances. The flame retardant begins to decompose at about 355°C, producing nitrogen-containing inert gas and polyphosphoric acid. The inert gas can effectively dilute the oxygen and combustible gas in the gas phase, playing a role in gas phase flame retardancy; while polyphosphoric acid can promote the formation of an expandable carbon layer in the polymer matrix, effectively isolating the heat and mass transfer in the condensed phase, and playing a role in condensed phase flame retardancy. Through the gas phase-condensed phase synergistic mechanism, the flame retardant properties of polymer materials can be significantly improved.
[0027] Nano cobalt exhibits excellent electromagnetic shielding effect due to its excellent electrical conductivity and magnetism, and has good catalytic performance, can provide active sites, adsorb and activate melamine polyphosphate molecules, thereby reducing the activation energy of the decomposition reaction and accelerating the reaction. This allows melamine polyphosphate to decompose at a relatively low temperature (200-250°C), increases the rate of flame-retardant gas and carbon layer generation, and effectively prevents the spread of flames. However, since nano cobalt has a large specific surface area and high surface energy, it is easy to agglomerate, and traditional mechanical means are difficult to effectively disperse it again. In addition, nano cobalt has poor compatibility with polymer materials, which further aggravates the agglomeration problem. To solve these problems, the present invention uses oleic acid to modify and protect nano cobalt. Oleic acid contains unsaturated double bonds and carboxyl groups, which can form a monomolecular film with nano cobalt, and is coated on the surface of metal nano cobalt in the form of ionic bonds, increasing the distance between nano cobalt particles and electrostatic repulsion, and preventing agglomeration between particles. At the same time, when compounded with the matrix resin, the unsaturated double bonds in oleic acid can be opened by the action of an initiator or heat or mechanical energy, and a series of chemical reactions such as grafting and crosslinking with the polyurethane matrix occur, further promoting better combination of nano cobalt and the polyurethane matrix. On the other hand, nano cobalt is easily oxidized, which affects its electrical conductivity and catalytic activity. Therefore, the present invention forms a structure of polythiophene-coated nano cobalt through in-situ polymerization of thiophene and oleic acid-nano cobalt. Since polythiophene has good electrical conductivity, compared with other polymer materials, coating nano cobalt will not affect its electrical conductivity.
[0028] Graphene has become an excellent conductive material with its extremely high electrical conductivity. Adding graphene to polyurethane foam can significantly improve the conductivity of the material. Compared with traditional carbon black conductive additives, the use of graphene can greatly reduce the amount of addition while maintaining the mechanical properties of polyurethane foam. The present invention uses three-dimensional graphene foam as a carrier to load nano-cobalt in its gaps and interlamellar. The conjugated π orbitals in the polythiophene molecular structure can be adsorbed with the conjugated regions in the graphene molecular structure through π-π interactions, so that nano-cobalt can be stably loaded on graphene. Finally, the graphene-loaded nano-cobalt conductive agent is cross-linked with melamine polyphosphate, so that it can stably play a synergistic flame retardant role in the polyurethane matrix.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] In the foaming process of the present invention, the selection and dosage of the foaming agent and the foam stabilizer are precisely controlled to ensure that a uniform and stable bubble structure is formed inside the foam. The uniform bubble distribution ensures that the foam is lightweight while maintaining sufficient flexibility and durability. By precisely controlling the foaming temperature (such as 80-85°C) and time (20-30 minutes), a uniform foaming effect can be obtained to ensure the compression resilience and structural stability of the foam. The aging process is carried out at a relatively low temperature (such as 40-60°C) to eliminate the residual stress in the foam and stabilize the internal structure of the foam. The control of the aging time allows the molecular chains of the foam to be fully cross-linked, thereby improving the mechanical properties of the foam, especially the durability and anti-compression resilience. This cross-linking process enhances the overall strength and durability of the foam, while reducing the deformation or fatigue of the foam during long-term use. By optimizing the foaming process and the aging process, the present invention controls the bubble structure of the foam, stabilizes the cross-linking inside the material, and makes it excellent in flexibility, durability and compression resilience. These mechanical properties enable the foam to adapt to the fitting needs of different shapes and sizes, while showing good adaptability and durability in practical applications.
[0031] In the foam preparation process of the present invention, graphene and nano-metal cobalt are used instead of carbon black as conductive agents, which reduces the amount of conductive agent added in the polyurethane foam and improves the mechanical properties of the foam.
[0032] The present invention uses nano-nickel to synergistically flame retard melamine polyphosphate, so that the limiting oxygen index reaches 33%, and the flame retardant grade reaches UL94-HF1.
[0033] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0035] Figure 1 It is a schematic diagram of the process of the preparation method of the present invention. DETAILED DESCRIPTION
[0036] The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments, unless otherwise described, they can be replaced by other equivalent or alternative features with similar purposes. Unless otherwise described, each feature is just an example in a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by ordinary technicians in the field. In the following examples, unless otherwise specified, concentration % refers to mass percentage; the substances used can be obtained commercially. The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments, unless otherwise described, they can be replaced by other equivalent or alternative features with similar purposes. Unless otherwise described, each feature is just an example in a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by ordinary technicians in the field.
[0037] The reagents used in the present embodiment and comparative examples are as follows. Those skilled in the art can select appropriate reagents for substitution, which can also achieve the limitations of the present invention. The following reagent selection is not used to limit the present invention.
[0038] The polyether polyol was purchased from Shanghai Baiang Chemical Technology Co., Ltd. The model number was 1030, the hydroxyl value was 230-250 mgKOH / g, and the number average molecular weight was 1500-2000.
[0039] Isocyanate was purchased from Wanhua Chemical, hexamethylene diisocyanate, with a purity of 99%.
[0040] Oleic acid was purchased from Nanjing Shuguang Chemical Factory.
[0041] Graphene foam was purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd. with a porosity of 97% and a C / O atomic ratio of 40.
[0042] Nano-cobalt was purchased from Zhejiang Yamei Nanotechnology Co., Ltd. with a purity of 99.99% and an average particle size of 20 nm.
[0043] Thiophene was purchased from Suzhou Yaco Technology Co., Ltd.
[0044] Melamine polyphosphate was purchased from BASF, brand: Melapur 200-70 (N: 42%-44%, P: 12%-14%).
[0045] The conductive fabric is plain woven conductive fabric purchased from Guangdong Taikun New Material Technology Co., Ltd.
[0046] Figure 1 It is a schematic diagram of the process of the preparation method of the present invention.
[0047] The present invention provides a method for preparing a multifunctional conductive foam, comprising the following steps:
[0048] (1) A conductive agent is prepared by loading nano-cobalt on three-dimensional graphite foam, and then the conductive agent is cross-linked with melamine polyphosphate to prepare a flame retardant conductive agent.
[0049] (2) vacuum dehydrating the polyether polyol at 130-140° C. until the moisture content is no more than 0.5%, thereby obtaining a treated polyether polyol.
[0050] (3) Add 2-2.5 parts of a catalyst, 100 parts of a polyether polyol, and 1-5 parts of an antioxidant into a reaction kettle, and react at 220-240° C. for 1-2 hours to obtain a reaction material. The antioxidant may be selected from one of antioxidant 5057, antioxidant 168, and antioxidant 1010. The catalyst may be selected from one or more of stannous octoate, stannous isooctanoate, and dibutyltin dilaurate.
[0051] (4) Add 10-18 parts of flame retardant conductive agent, 25-35 parts of isocyanate, 1-2 parts of foaming agent and 2-5 parts of foam stabilizer to the reaction material for foaming, the foaming temperature is 80-85°C, the reaction time is 20-30 minutes, and a foam body is obtained, and the foam body is aged at 40-60°C to obtain foam; the foam stabilizer can be one or more of polyacrylamide and dimethyl silicone oil. The foaming agent can be water or a mixture of water and 1,1-dichloro-1-fluoroethane.
[0052] (5) Cut the foam into units with a width of 2 cm, a length of 10 cm, and a thickness of 0.3 cm; the size can be customized according to actual customer needs and is not limited here.
[0053] Use a bonding machine to bond the cut foam to a 40μm-120μm conductive cloth; in this embodiment, the conductive cloth is selected to be 80μm, and in other embodiments, any value between 40μm and 120μm can be selected; a 10-15μm thick adhesive layer pressure-sensitive adhesive is evenly applied to the side of the foam away from the conductive cloth. In this embodiment, the thickness of the pressure-sensitive adhesive is 10μm, and in other embodiments, any value between 10-15μm can be selected; then the foam with the pressure-sensitive adhesive is pressed onto a 20-30μm thick isolation layer release paper; in this embodiment, the thickness of the release paper is 20μm, and in other embodiments, the thickness of the release paper can also be selected from any value between 20-30μm, all of which can achieve the effect of the present invention and can be adjusted to a certain extent according to market demand, and is not used to limit the scope of protection of the present invention.
[0054] After completing the above steps, the multifunctional foam is obtained.
[0055] Specific examples of foam preparation are listed below to further illustrate the present invention.
[0056] Example 1
[0057] S1: Take 2 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 30 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 12:1.
[0058] S2: Ultrasonic dispersion of 2 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 5 parts of thiophene and 0.1 parts of hydrogen peroxide, stirring and reacting at 40°C for 40 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.
[0059] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 2 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of the pre-treated graphene and 2 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.1 parts of sodium sulfite to the reactor, stir the reaction for 30 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol twice and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.
[0060] S4: 30 parts of melamine polyphosphate, 8 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 50°C for 3 hours, centrifuged for solid-liquid separation, and then washed with ethanol and dried to obtain a flame retardant conductive agent.
[0061] The polyether polyol was dehydrated under vacuum at 130° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.
[0062] 2 parts of catalyst stannous octoate, 100 parts of polyether polyol and 1 part of antioxidant 1010 were added into a reaction kettle, and reacted at 220° C. for 1 hour to obtain a reaction material.
[0063] 10 parts of flame retardant conductive agent, 25 parts of isocyanate, 1 part of foaming agent water and 2 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 80° C. and a reaction time of 20 min to obtain a foamed body.
[0064] The foamed body was aged at 40°C to obtain foam.
[0065] Example 2
[0066] S1: Take 4 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 60 minutes, filter and wash the product with anhydrous ethanol for 3 times and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 20:1.
[0067] S2: Ultrasonic dispersion of 4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 8 parts of thiophene and 0.2 parts of hydrogen peroxide, stirring and reacting at 60°C for 60 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.
[0068] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 5 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of the pre-treated graphene and 4 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.3 parts of sodium sulfite to the reactor, stir the reaction for 60 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol three times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.
[0069] S4: 40 parts of melamine polyphosphate, 10 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 70°C for 6 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.
[0070] The polyether polyol was dehydrated under vacuum at 140° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.
[0071] 2.5 parts of catalyst stannous isooctanoate, 100 parts of polyether polyol, and 5 parts of antioxidant 168 were added into a reaction kettle, and reacted at 240° C. for 2 hours to obtain a reaction material.
[0072] 18 parts of flame retardant conductive agent, 35 parts of isocyanate, 2 parts of a mixture of water and 1,1-dichloro-1-fluoroethane (9:2) as a blowing agent and 5 parts of polyacrylamide as a foam stabilizer were added to the reaction material for foaming at a foaming temperature of 85° C. and a reaction time of 30 min to obtain a foamed body.
[0073] The foamed body was aged at 60°C to obtain foam.
[0074] Example 3
[0075] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 15:1.
[0076] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.
[0077] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.
[0078] S4: 35 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.
[0079] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.3%, thereby obtaining a treated polyether polyol.
[0080] 2.3 parts of catalyst dibutyltin dilaurate, 100 parts of polyether polyol, and 2 parts of antioxidant 5057 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.
[0081] 14 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 4 parts of foam stabilizer polyacrylamide were added to the reaction material for foaming at a foaming temperature of 82° C. and a reaction time of 25 min to obtain a foamed body.
[0082] The foamed body was aged at 50°C to obtain foam.
[0083] Example 4
[0084] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 18:1.
[0085] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.
[0086] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.
[0087] S4: 38 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.
[0088] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.
[0089] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.
[0090] 16 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 3 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.
[0091] The foamed body was aged at 50°C to obtain foam.
[0092] Comparative Example 1
[0093] S2: Ultrasonic dispersion of 3 parts of nano-cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano-cobalt.
[0094] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.
[0095] S4: 38 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.
[0096] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.
[0097] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.
[0098] 16 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 3 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.
[0099] The foamed body was aged at 50°C to obtain foam.
[0100] Compared with Example 4, Comparative Example 1 omitted the process of treating the nano-cobalt powder with oleic acid in step S1, and the other process parameters and conditions were the same.
[0101] Comparative Example 2
[0102] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 18:1.
[0103] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of acrylamide and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polyacrylamide-coated nano cobalt.
[0104] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polyacrylamide-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol three times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.
[0105] S4: 38 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.
[0106] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.
[0107] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.
[0108] 16 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 3 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.
[0109] The foamed body was aged at 50°C to obtain foam.
[0110] Comparative Example 2 Compared with Example 4, acrylamide was used instead of thiophene to coat the nano-cobalt, and the other process parameters and conditions were the same.
[0111] Comparative Example 3
[0112] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 18:1.
[0113] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.
[0114] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.
[0115] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.
[0116] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.
[0117] 16 parts of a mixture of melamine polyphosphate and a conductive agent (in a ratio of 38 to 10), 30 parts of isocyanate, 1.5 parts of water as a foaming agent and 3 parts of dimethyl silicone oil as a foam stabilizer were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.
[0118] The foamed body was aged at 50°C to obtain foam.
[0119] Compared with Example 4, in Comparative Example 3, the process of cross-linking melamine polyphosphate with the conductive agent in step S4 is omitted, and the other process parameters and conditions are the same.
[0120] The foams in Examples 1-4 and Comparative Examples 1-3 were subjected to performance testing;
[0121] The flame retardant performance test is as follows:
[0122] The limiting oxygen index (LOI) was determined according to GB / T2406-1993; an oxygen index measuring instrument HC-2 was purchased from the Nanjing Jiangning District Analytical Instrument Factory.
[0123] The horizontal combustion test of UL94 foam material refers to GB / T8332-2008, and the horizontal combustion tester CZF-3 is purchased from Nanjing Jiangning District Analytical Instrument Factory.
[0124] Conductivity test: The test was carried out using a FT-3120 four-probe measuring instrument purchased from Ningbo Ruikewei Intelligent Technology Co., Ltd.
[0125] Conductivity: Connect the two ends of the test sample to the positive and negative electrodes of the electrochemical workstation with copper wires, call the single potential step chronoamperometry, set the measurement voltage U=10V, the measurement time is 10s, take the average value after the current curve stabilizes, and calculate the conductivity.
[0126] The performance test results are shown in Table 1 below.
[0127] Table 1 - Performance test data
[0128]
[0129] As can be seen from Table 1, due to the lack of the step of activating nano-cobalt with oleic acid in Comparative Example 1, the nano-cobalt agglomerates and cannot exert its electrical conductivity and catalytic decomposition of melamine polyphosphate, resulting in poor flame retardancy and electrical conductivity.
[0130] In Comparative Example 2, since the nano-cobalt is wrapped with polyacrylamide, compared with Example 4 which is coated with polythiophene, the polyacrylamide has poor conductivity and cannot exert the conductive properties of the nano-materials, resulting in a decrease in its conductivity. On the other hand, polyacrylamide lacks conjugated π orbitals and has poor compatibility with graphene loading, resulting in a low actual nano-cobalt content in the conductive agent, resulting in insufficient synergistic flame retardancy and a decrease in flame retardancy.
[0131] Comparative Example 3 lacks the step of cross-linking the flame retardant and melamine polyphosphate, resulting in the two components being dispersed in the polyurethane matrix, and the synergistic effect is reduced, thereby reducing its flame retardant properties, but still has good conductive properties.
[0132] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a multifunctional conductive foam, characterized in that: The following steps are involved: (1) A conductive agent is prepared by loading nano-cobalt on three-dimensional graphite foam, and then the conductive agent is cross-linked with melamine polyphosphate to prepare a flame retardant conductive agent; (2) vacuum dehydrating the polyether polyol at 130-140° C. until the moisture content is no more than 0.5%, thereby obtaining a treated polyether polyol; (3) adding 2-2.5 parts of a catalyst, 100 parts of a polyether polyol, and 1-5 parts of an antioxidant into a reaction kettle, and reacting at 220-240° C. for 1-2 hours to obtain a reaction material; (4) adding 10-18 parts of flame retardant conductive agent, 25-35 parts of isocyanate, 1-2 parts of foaming agent and 2-5 parts of foam stabilizer to the reaction material for foaming at a foaming temperature of 80-85° C. for a reaction time of 20-30 min to obtain a foamed body, and subjecting the foamed body to a aging treatment at 40-60° C. to obtain a foam; (5) using a bonding machine to bond the foam to the conductive cloth; evenly applying an adhesive layer on the side of the foam away from the conductive cloth, and then pressing the foam with the adhesive layer onto the isolation layer to obtain the multifunctional conductive foam; The specific preparation process of the flame retardant conductive agent is as follows: S1: 2-4 portions of nano-cobalt powder are put into a reactor, and a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9 is added, followed by ultrasonic dispersion. After reacting for 30-60 minutes, the product is filtered and washed with anhydrous ethanol for 2-3 times, and then vacuum dried to obtain oleic acid-nano-cobalt; the mass ratio of the nano-cobalt powder to oleic acid is 12-20:1; S2: ultrasonically dispersing 2-4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 5-8 parts of thiophene and 0.1-0.2 parts of hydrogen peroxide, stirring and reacting at 40-60° C. for 40-60 minutes, and then performing solid-liquid separation, washing the obtained solid with ethanol and drying it to obtain polythiophene-coated nano cobalt; S3: pre-treating the three-dimensional graphene foam in an air atmosphere for 2-5 minutes in a plasma treatment machine, then rinsing with anhydrous ethanol and drying for standby use; ultrasonically dispersing 10 parts of the pre-treated graphene and 2-4 parts of the polythiophene-coated nano-cobalt in a reactor containing 100 parts of an ethanol aqueous solution and stirring them evenly, then adding 0.1-0.3 parts of sodium sulfite to the reactor, stirring the reaction under a nitrogen atmosphere for 30-60 minutes, then filtering and washing the solid with anhydrous ethanol 2-3 times and then vacuum drying; A graphene-loaded nano-cobalt conductive agent is obtained; S4: ultrasonically disperse 30-40 parts of melamine polyphosphate, 8-10 parts of resorcinol and 10 parts of the conductive agent in acetone, uniformly react at 50-70°C for 3-6 hours, centrifuge for solid-liquid separation, then wash with ethanol and dry to obtain a flame retardant conductive agent.
2. The method for preparing a multifunctional conductive foam according to claim 1, characterized in that: The conductive fabric layer is plain woven conductive fabric with a thickness of 40 μm-120 μm.
3. The method for preparing a multifunctional conductive foam according to claim 1, characterized in that: The adhesive layer is a pressure-sensitive adhesive or a hot-melt adhesive, and has a thickness of 10-15 μm.
4. The method for preparing a multifunctional conductive foam according to claim 1, characterized in that: The isolation layer is release paper with a thickness of 20-30 μm.
5. The method for preparing a multifunctional conductive foam according to claim 1, characterized in that: The antioxidant is one of antioxidant 5057, antioxidant 168 and antioxidant 1010.
6. The method for preparing a multifunctional conductive foam according to claim 1, characterized in that: The foam stabilizer is one or more of polyacrylamide and dimethyl silicone oil.
7. The method for preparing a multifunctional conductive foam according to claim 1, characterized in that: The catalyst is one or more of stannous octoate, stannous isooctanoate and dibutyltin dilaurate.
8. The method for preparing a multifunctional conductive foam according to claim 1, characterized in that: The blowing agent is water or a mixture of water and 1,1-dichloro-1-fluoroethane.
Citation Information
Patent Citations
Multifunctional conductive foam
CN118813157A